PENINGKATAN KAPASITAS PRODUKSI SANDAL SEPON MELALUI PENGGUNAAN ALAT PEREKAT LEM BERTENAGA MOTOR LISTRIK - Rofii, Faqih; Hermawan, Dadang; Tjahjono, Ngudi (DINAMIKA DOTCOM, 2016)
Craft slippers eva sponge widely grown in Malang, one of them in the village Gunungrejo Singosari. In the process of making sandals, there are several issues, including the process of gluing and gluing glue. At this stage of gluing, gluing process with emphasis sponge eva glue between the top, middle, bottom and rope sandals done in a simple / manual so that less precision, less strong adhesive power and take a long time. As the solution of the problems described above, it was designed and created tools for sizing and adhesive glue, along with the increase in workforce skills in the operation of the equipment. With the implementation of these tools, the ability of partners in producing sponge eva slippers increased from 7-10 scores / day to 25 -30 scores / day, or 600-750 scores / month, where 1 score was 20 pairs of sandals or increased three times from the previousÂ Keywords: sandal spon, pengeleman, perekat lem